Exploring students' perceptions and the significance of social and cognitive presence in their educational voyage (Journal of Applied Learning and Teaching, 2024)
The purpose of this study was to examine students’ perspectives on the importance of social and cognitive presence throughout their educational experience. Four hundred and fifty fourth-year education-major students from five universities in Southern Nigeria participated in the research. We adopted a correlational research design using the survey approach. A questionnaire of the four-point Likert variety was used for data collection. The data obtained were subjected to simple linear regression and Pearson product-moment correlation analysis. The study’s findings demonstrate a positive relationship between students’ evaluations of their social presence and their academic success. Also, a strong correlation between cognitive presence, student involvement and critical thinking was found. In addition, the current study revealed a significant association between students’ total educational experiences and their degrees of social and cognitive presence. These findings have implications for educational methods, emphasizing the value of encouraging social connection, cognitive engagement, and the fusion of educational opportunities. The knowledge acquired from this study will help researchers, educators, and policymakers develop more effective curricula and improve teaching methods, which will ultimately help students perform better overall.